Chronic Adenotonsillitis as a Cause of Airway Obstruction: A Case Report - Anggie Astifany Azizah Salim; Andi Tenri Sanna; Jane Mary Carolina (Newinera Publisher, 2026)
Chronic adenotonsillitis is a chronic inflammation of the palatine tonsils and adenoid tissue that lasts for more than three months or recurs several times a year. Chronic adenotonsillitis accompanied by enlargement of the adenoid tissue can cause airway obstruction. A 14-year-old boy came to the ENT clinic with a main complaint of pain when swallowing for the past ±3 months, which was intermittent, especially when swallowing hard or hot food. The complaint was accompanied by itching and discomfort in the throat and bad breath. The patient also experienced mild fever recurring every 2–3 days. In addition, the patient complained of chronic nasal congestion, especially at night, accompanied by thick mucus, mouth breathing, and loud snoring during sleep. Physical examination by pharyngoscopy revealed T2-T2 tonsils with widened crypts and an uneven surface, as well as visible adenoids. The patient was diagnosed with Chronic Adenotonsillitis and scheduled for surgical intervention. This case shows that chronic adenotonsillitis can cause airway obstruction. Based on theory, chronic adenotonsillitis is often accompanied by enlarged adenoid tissue that causes obstruction of the upper airway, leading to symptoms such as chronic nasal congestion, mouth breathing, and snoring during sleep. In this case, the patient presented with the same complaints, namely chronic nasal congestion and loud snoring during sleep. The habit of breathing through the mouth and restless sleep also indicated nasopharyngeal obstruction due to adenoid hypertrophy. Recurrent infections can cause chronic adenotonsillitis and lead to adenoid hypertrophy and tonsil hypertrophy, resulting in symptoms such as snoring and mouth breathing, as well as complications like posterior nares obstruction, perituba lymphadenitis, and otitis media.